Roles of Post-translational Modifications in Spinocerebellar Ataxias - Wan, Linlin; Xu, Keqin; Chen, Zhao; Tang, Beisha; Jiang, Hong (Frontiers in Cellular Neuroscience, 2018)
Post-translational modifications (PTMs), including phosphorylation, acetylation, ubiquitination, SUMOylation, et al, of proteins are vital regulation mechanisms for multiple cellular processes and modulate protein properties such as intracellular distribution, activity, stability, aggregation and interactions. Spinocerebellar ataxias (SCAs) are hereditary, heterogeneous, neurodegenerative diseases for which the primary manifestation involves ataxia. Because the pathogenesis of most SCAs is correlated with mutant proteins, the PTMs of disease-related proteins might functionally affect SCA development and represent potential therapeutic interventions. Here, we review multiple PTMs related to disease-causing proteins in SCA pathogenesis and their effects. Further, We discuss these PTMs as potential targets for treating SCAs and describe translational therapies targeting PTMs that have been published.